Perlindungan Hukum Terhadap Watu Jaran Tanpa Kepala DiDesa Laren Kecamatan Bumiayu, Kabupaten BrebesBerdasarkan Undang-Undang Nomor 11 Tahun 2010 tentangCagar Budaya - Rafie Azhar Hibatullah; Martiningsih (Wijayakusuma Law Review, 2023)
Abstract The Headless Watu Jaran is a historical site which is also a Suspected Cultural Heritage Object (ODCB)which has not been designated as a Cultural Conservation located in Laren Village, Bumiayu District, BrebesRegency. Law Number 10 of 2011 concerning Cultural Conservation guarantees legal certainty and protection forOCBD. The formulation of the problem is what form of legal protection for cultural heritage in Brebes Regencybased on Law (UU) Number 11 of 2010 concerning cultural heritage and what are the obstacles in legal protectionof the Headless Watu Jaran in Laren Village, Bumiayu District, Brebes Regency. Normative juridical research withdescriptive-qualitative. Data source is secondary data. Primary legal materials include Law Number 11 of 2010,Government Regulation Number 10 of 1993 and Brebes Regency Regional Regulation Number 10 of 2015. The datacollection techniques areobservation, interview and literature study. Research results: a) Law Number 11 of 2010contains legal protection and legal certainty as well as Regional Regulation (Perda) of Brebes Regency Number 10of 2015 concerning the Preservation and Management of Cultural Heritage and concrete efforts by the Governmentof Laren Village, Bumiayu District, Brebes Regency in protecting and preserving cultural heritage includes,Reporting on the discovery of Suspected Cultural Conservation Objects, care/maintenance, buildingperimeter/barrier fences, socialization and optimization for various interests. b) Obstacles include a minimumnumber of experts, regional performance is hampered because the Cultural Preservation Center is not optimal,synergy between the central government, provincial government, district/city government and village governmentand the community has not reached standards and there are still problems, legal sanctions have not been strictlyenforced.